Inicjatywa obywatelska w praktyce politycznej III RP - Andrzej Piasecki (In Gremium. Studies in History, Culture and Politics, 2009)
Civil initiative in the political experience in the Third Republic of PolandThis article is devoted to the description of the functioning of direct democracy mechanisms providedfor in the political system of the Third Republic of Poland. The author concentrates mostłyon the definitional consideration referring to the institution of civil initiative (public). Later, theauthor carries out an anałysis of the implementation process of this form of direct democracy inthe Polish legal system, which was initiated in local communities.